Dependence of scrape-off layer profiles and turbulence on gas fuelling in high density H-mode regimes in TCV. (1st September 2022) - Stagni, A.; Vianello, N.; Tsui, C.K.; Colandrea, C.; Gorno, S.; Bernert, M.; Boedo, J.A.; Brida, D.; Falchetto, G.; Hakola, A.; Harrer, G.; Reimerdes, H.; et al.
Abstract: A set of high density, highly shaped H-mode discharges has been performed in the TCV tokamak with the aim of assessing the effects of increasing divertor neutral recycling on the properties of upstream inter-ELM scrape-off layer (SOL) profiles and transport. An increase of divertor neutral pressure has been correlated with the evolution of separatrix properties and turbulence level. The latter has been quantified by means of the α t parameter introduced in (Eich 2020 Nucl. Fusion 60 056016), describing the contribution of resistive-interchange turbulence in the SOL relative to drift wave transport. The analysis reveals a general broadening of the upstream SOL profiles as α t increases, with the SOL power width measured by the vertical IR thermography system increasing significantly. In a similar way, the upstream density profile widens in the near SOL, whereas in the far SOL a density shoulder is observed to progressively form and increase in amplitude. This behaviour is associated with an enhancement of far SOL turbulent transport in the form of blob-filaments travelling radially faster across the far SOL and becoming bigger at higher α t . The detected filaments, evaluated from the fast reciprocating probe at the outer midplane, are determined to mostly belong to the resistive ballooning and resistive X-point regimes.